2013
DOI: 10.1118/1.4794929
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐specific QA for IMRT should be performed using software rather than hardware methods

Abstract: OVERVIEWMeasurement-based patient-specific quality assurance (QA) for IMRT is both time-consuming and potentially inaccurate, since the measurements are made in phantoms rather than actual patients. It has been suggested that it would be more accurate and considerably less time consuming to perform such QA with software rather than hardware, and this is the topic debated in this month's Point/Counterpoint.Arguing for the Proposition is Alfredo Siochi, Ph.D. Dr. Siochi received his Ph.D. in Physics from Virgini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
55
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 12 publications
0
55
0
Order By: Relevance
“…IMRT planar QA is a time‐consuming and potentially inaccurate method (20) . Some studies showed the result of planar QA could not predict clinically relevant patient dose error 21 , 22 , 23 , 24 .…”
Section: Discussionmentioning
confidence: 99%
“…IMRT planar QA is a time‐consuming and potentially inaccurate method (20) . Some studies showed the result of planar QA could not predict clinically relevant patient dose error 21 , 22 , 23 , 24 .…”
Section: Discussionmentioning
confidence: 99%
“…It is a subject of ongoing debate,31 with the latest TG‐218 report29 acknowledging but not adjudicating the issue. We characterize the approach described in this paper as semi‐empirical or hybrid, as some of the information (MLC apertures) is derived from independent measurements, while other elements are harvested from the accelerator log files.…”
Section: Discussionmentioning
confidence: 99%
“…Mobius utilizes the delivery information, reported in the log‐file, when calculating dose within the MobiusFX module. There is an ongoing discussion within the medical physics community regarding the validity of log‐file analysis for patient‐specific quality assurance (QA) of modulated treatment beams 10, 11, 12. Publications examining the reliability and effectiveness of this QA method are available for review 13, 14, 15, 16, 17, 18, 19, 20…”
Section: Introductionmentioning
confidence: 99%